Safety Performance Of Subcontractors In The Palestinian Construction Industry - Enshassi, Adnan; Choudhry, Rafiq M.; Mayer, Peter E.; Shoman, Younis (Penerbit Universiti Sains Malaysia, 2008)
Subcontractors perform most of the construction works and their effect on industry are apparent in different activities of construction. Therefore, subcontractors need more attention from government and contractors union. The aim of this paper is to identify, evaluate, and rank factors that influence safety performance of subcontractors in the Gaza Strip (Palestine) according to their relative importance. The study concluded that reported accident rates will decrease among subcontractors and their workers if new workers are trained well in the work site and they are informed about dangerous places, and if a workable safety plan is well preplanned. The results also showed that reported accident rates increased among subcontractors when using old, unsafe equipment and due to the complexity or difficulty in the construction sites features. Owners and general contractors need to stipulate strict clauses for safety in the contract for improving safety record of subcontractors. Construction workers must receive proper job related safety and health training with a safety logbook. It is recommended that the subcontractors and workers should attend continuing safety programs on regular basis as part of their perquisite to work in construction sites.